Rekonstruksi Teori Humanistik dalam Pembelajaran Era Digital: Kajian Konseptual dan Implementatif terhadap Pengembangan Potensi Peserta Didik - Mohammad Mohan; Hurul Ain; M.Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to reconstruct humanistic learning theory to remain relevant in the digital era by integrating human values and technology. The main issue is the tendency of digital learning to emphasize efficiency and academic achievement while neglecting students’ emotional and psychological needs. This research uses a qualitative approach through a literature review of humanistic theory, constructivism, and digital learning. The findings show that applying humanistic approaches in personalized e-learning, blended learning, and artificial intelligence can enhance students’ motivation, independence, and meaningful learning. However, excessive reliance on technology without a humanistic approach may lead to dehumanization in education. This study proposes the concept of Humanistic Digital Learning as a model that integrates humanistic values, active learning processes, and digital technology in a balanced way to ensure student-centered and meaningful learning.